2008
DOI: 10.1037/a0012835
|View full text |Cite
|
Sign up to set email alerts
|

Learning (not) to talk about race: When older children underperform in social categorization.

Abstract: The present research identifies an anomaly in sociocognitive development, whereby younger children (8 and 9 years) outperform their older counterparts (10 and 11 years) in a basic categorization task in which the acknowledgment of racial difference facilitates performance. Though older children exhibit superior performance on a race-neutral version of the task, their tendency to avoid acknowledging race hinders objective success when race is a relevant category. That these findings emerge in late childhood, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
153
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 49 publications
9
153
0
Order By: Relevance
“…Children with high ToSM were able to use this understanding to inform their exclusion judgments of individual group members. This finding suggests that ToSM may be important to children's ability to understand group norms about showing explicit bias and their control of explicit intergroup bias (Rutland, 2004;Rutland et al, 2005;Apfelbaum et al, 2008).…”
Section: Studymentioning
confidence: 89%
See 1 more Smart Citation
“…Children with high ToSM were able to use this understanding to inform their exclusion judgments of individual group members. This finding suggests that ToSM may be important to children's ability to understand group norms about showing explicit bias and their control of explicit intergroup bias (Rutland, 2004;Rutland et al, 2005;Apfelbaum et al, 2008).…”
Section: Studymentioning
confidence: 89%
“…Developmental psychologists have recently begun to demonstrate that group norms affect young children's explicit ethnic intergroup attitudes (Apfelbaum, Pauker, Ambady, Sommers, & Norton, 2008;Rutland, 2004;Rutland et al, 2005;Rutland et al, 2007). For example, found that 7-year-old children only showed explicit ethnic prejudice when either a pro-prejudice norm and/or an out-group threat was made salient.…”
Section: Studymentioning
confidence: 99%
“…Additionally, children in Western society recognize that expressing negative racial attitudes or even acknowledging racial differences can reflect poorly on them and so they learn to inhibit their judgments based on race between the ages of 8 and 10 years old (Apfelbaum et al, 2008;Rutland, Cameron, Milne, & McGeorge, 2005). Taken together, these studies suggest that, around age 8 or 9, children have an understanding of the factors that go into impression formation, modify their own behaviors, and know that others should modify their behaviors in service of appearing favorably to others.…”
Section: A Developing Sense Of Wanting To Appear Fair?mentioning
confidence: 99%
“…presentation increasing as they approach eight to ten years of age (Aloise-Young, 1993;Apfelbaum, Pauker, Ambady, Sommers, & Norton, 2008;Banerjee, 2002;Piaget, 1932;Selman, 1980;Turiel, 2006). Interestingly, children become increasingly concerned with how they appear to others at the same time as they are becoming more concerned with being fair.…”
mentioning
confidence: 99%
“…1, 2007), and standard school curricula (e.g., activities and readings that convey a generalized cultural identity, but leave group differences unaddressed; Tatum, 2003). Color blindness is also expressed through teachers' strategies for promoting equality in classrooms (e.g., routinely emphasizing that "race does not matter" and "we are all the same"; Pollock, 2004), and even by behavioral changes among students themselves (e.g., a learned tendency to avoid mentioning race, even when clearly useful, beginning around 10 years of age; Apfelbaum, Pauker, Ambady, Sommers, & Norton, 2008).…”
mentioning
confidence: 99%